2018
DOI: 10.21834/jabs.v5i18.91
|View full text |Cite
|
Sign up to set email alerts
|

The Malay Mothers' Perspective on the Usage of Galactagogue

Abstract: Breastfeeding confers a lot of benefits to both mother and child. Problems such as insufficient milk production may affect the mothers’ breastfeeding process and most mothers opt to consider on using galactagogue. We collected and analyzed questionnaire consists of demographic data and usage patterns of herbal galactagogue during lactating. To summarize, most mothers consume herbal galactagogue due to lack of milk production. A larger scale survey of herbal galactagogues used would be beneficial in future to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
1
2
1
Order By: Relevance
“…The extent to which Iranian physicians prescribe TCIM products and consider them to be effective has been investigated in prior studies [35]. In comparison, the highest proportion of recommendations regarding the use of complementary medicine came from friends in the Malaysian study (60%) and from family in the Australian study (61.5%), showing consistency with our data [2,33]. In Italy, however, obstetricians/gynecologists made the most TCIM recommendations (44%) [28].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The extent to which Iranian physicians prescribe TCIM products and consider them to be effective has been investigated in prior studies [35]. In comparison, the highest proportion of recommendations regarding the use of complementary medicine came from friends in the Malaysian study (60%) and from family in the Australian study (61.5%), showing consistency with our data [2,33]. In Italy, however, obstetricians/gynecologists made the most TCIM recommendations (44%) [28].…”
Section: Discussionsupporting
confidence: 86%
“…Interestingly, we found that 36.6% of breastfeeding mothers using TCIM were employed, which is less than the gures reported in the United States (56%), Malaysia (89.2%), and Sierra Leone (52.1%) [16,25,33]. On the other hand, our multivariable regression analysis showed that working mothers used TCIM about 75% less than housewives.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations